Aikeqing decreases viral loads in SHIV89.6-infected Chinese rhesus macaques. Issue 1 (December 2016) - Zhang, Gao-Hong; Han, Jian-Bao; Zhu, Lin; Luo, Rong-Hua; Zhang, Xi-He; Chen, Xin; Hu, Ying-Jie; Fu, Lin-Chun; Zheng, Yong-Tang
Abstract Background Aikeqing (AKQ) has been shown in clinical studies to improve quality of life of HIV/AIDS patients, but anti-HIV activity has not been determined. The SHIV-infected macaque is an important animal model for testing antiviral drugs. This study aimed to determine the anti-HIV activity of AKQ in chronically SHIV89.6-infected Chinese rhesus macaques. Methods Nine Chinese rhesus macaques were inoculated intravenously with SHIV89.6 virus. At 11 weeks post-infection, the animals were arbitrarily divided into three groups: high-dose (AKQ 1.65 g/kg;n = 3), low-dose (AKQ 0.55 g/kg;n = 3), and control (water 1 mL/kg;n = 3). Treatment was administered by the intragastric gavage route once-daily for 8 weeks. Blood (5 mL) was collected biweekly. Viral loads were analyzed by real-time quantitative RT-PCR assays, and T cell counts were monitored by FACS analyses throughout the treatment. Results AKQ induced a persistent decline (P = 0.02) in plasma viral loads during treatment in the high-dose group compared with their baseline levels, and cessation of the therapy caused viral load rebound to the pretreatment levels. No significant difference (P = 0.06) was found in the plasma viral loads during treatment in the low-dose group. The CD4+ T cell counts and CD4/CD8 ratios remained at stable high levels during the treatment period. Conclusion AKQ reduced plasma viral loads in the SHIV89.6-infected Chinese rhesus macaque model.